2016
DOI: 10.18632/oncotarget.11614
|View full text |Cite
|
Sign up to set email alerts
|

Rottlerin exerts its anti-tumor activity through inhibition of Skp2 in breast cancer cells

Abstract: Studies have investigated the tumor suppressive role of rottlerin in carcinogenesis. However, the molecular mechanisms of rottlerin-induced anti-tumor activity are largely unclear. Skp2 (S-phase kinase associated protein 2) has been validated to play an oncogenic role in a variety of human malignancies. Therefore, inactivation of Skp2 could be helpful for the treatment of human cancers. In the current study, we explore whether rottlerin could inhibit Skp2 expression, leading to inhibition of cell growth, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 42 publications
(52 reference statements)
2
32
0
Order By: Relevance
“…Curcumin has been demonstrated to inhibit the expression of Skp2 in several human cancer types (17,38,39). Rottlerin exhibited its anti-tumor activity by the inhibition of Skp2 in breast cancer and pancreatic cancer cells (18,40). The present study demonstrated that PF inhibited Skp2 expression in liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been demonstrated to inhibit the expression of Skp2 in several human cancer types (17,38,39). Rottlerin exhibited its anti-tumor activity by the inhibition of Skp2 in breast cancer and pancreatic cancer cells (18,40). The present study demonstrated that PF inhibited Skp2 expression in liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The following thermocycling conditions were used for qPCR: Initial denaturation at 95˚C for 10 min; 45 cycles of 95˚C for 15 sec, 60˚C for 1 min; and a final extension at 72˚C for 5 min. Relative expression levels were quantified using the 2 -ΔΔCq method as previously described (18,19), and normalized to the internal reference gene GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…A study reported that quercetin, curcumin and lycopene downregulated Skp2 expression, leading to promotion of cell cycle arrest in breast cancer cells [5]. Rottlerin, a polyphenolic substance in the fruits of mallotus philippinensis, exerts its anticancer activity via the suppression of Skp2 in breast and pancreatic cancer cells [6,7]. Nitidine chloride, a bioactive phytochemical alkaloid, was found to repress the expression of Skp2 in ovarian cancer cells.…”
mentioning
confidence: 99%
“…Cells (3x10 5 cells/well) were cultured in a 6-well plate overnight and treated with the various concentrations of rottlerin for 48 h. Following treatment, the cells were harvested and washed with PBS, resuspended (1x10 5 cells) in 500 µl binding buffer with 5 µl propidium iodide (PI) and 5 µl FITC-conjugated anti-Annexin V antibody. Apoptosis was analyzed on a flow cytometer (BD Biosciences, Franklin Lakes, NJ, USA) as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were incubated with 0.1 mg/ml RNase I and 50 mg/ml PI at 37˚C for 30 min. Cell cycle was analyzed on a flow cytometer (BD Biosciences) as described previously (18).…”
Section: Methodsmentioning
confidence: 99%